A Multiplexed Screening Assay to Evaluate Chemotherapy-Induced Myelosuppression Using Healthy Peripheral Blood and Bone Marrow. (August 2018) - Javarappa, Komal K.; Tsallos, Dimitrios; Heckman, Caroline A.
Myelosuppression is a major side effect of chemotherapy in cancer patients and can result in infections, bleeding complications, and increased risk of morbidity and mortality, as well as limit the drug dose and frequency of administration. Chemotherapy-induced myelosuppression is caused by the disruption of normal hematopoiesis. Thus, prior understanding of the adverse effects of chemotherapies on hematopoietic cells is essential to minimize the side effects of cancer treatment. Traditional methods such as colony-forming assays for studying chemotherapy-induced myelosuppression are time-consuming and labor intensive. High-throughput flow cytometry technologies and methods to detect rare hematopoietic cell populations are critical in advancing our understanding of how different blood cell types in complex biological samples respond to chemotherapeutic drugs. In the present study, hematopoietic progenitor cells were induced to differentiate into megakaryocytes and myeloid lineage cells. The expanded cells were then used in a multiplexed assay to monitor the dose-response effects of multiple chemotherapies on different stages of megakaryocyte differentiation and myeloid cell populations in a 96-well plate format. The assay offers an alternative method to evaluate the myelosuppressive potential of novel chemotherapeutic drugs compared to traditional lower throughput and labor-intensive assays.